2007
DOI: 10.1051/0004-6361:20066778
|View full text |Cite
|
Sign up to set email alerts
|

H2O maser emission from bright rimmed clouds in the southern hemisphere

Abstract: Context. Water maser emission is a powerful tracer of the presence of embedded sources in dense clouds since it requires elevated temperatures (>100 K) and densities (>10 7 cm −3 ) that can be found in circumstellar disks and/or jets/outflows associated with Young Stellar Objects. Bright rimmed clouds compressed by ionization fronts from nearby massive stars are considered good examples of externally triggered star formation, possibly resulting in the formation of massive stars. Aims. We aim to determine the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…We believe that this is not a sensitivity effect, but reflects an intrinsic property of BRCs as a class of clouds, in agreement with the initial results of the less sensitive studies by Valdettaro et al (2005Valdettaro et al ( , 2007 in both hemispheres. Interestingly, we note that a recent study of the OH maser emission toward 46 BRCs has also given largely negative results ( Thomas et al 2006).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We believe that this is not a sensitivity effect, but reflects an intrinsic property of BRCs as a class of clouds, in agreement with the initial results of the less sensitive studies by Valdettaro et al (2005Valdettaro et al ( , 2007 in both hemispheres. Interestingly, we note that a recent study of the OH maser emission toward 46 BRCs has also given largely negative results ( Thomas et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…This result puts on firmer ground the initial findings of less sensitive, single-dish studies of Valdettaro et al (2005Valdettaro et al ( , 2007. BRCs seem to produce mostly low-luminosity Class I objects, which are presently in a more advanced evolutionary phase than Class 0 sources for which the frequency of occurrence of maser emission is high, albeit highly variable.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…H 2 O masers have been found in regions of high-and low-mass star formation and therefore act as a good general sign post of star formation. The Valdettaro et al (2007) search of the southern SFO catalogue detected H 2 O maser emission towards 7 clouds; due to the inherent variability of H 2 O masers this is a lower limit. In addition to H 2 O masers we searched the methanol maser catalogue of Pestalozzi et al (2005) and found three clouds coincident with Class II maser emission.…”
Section: Star Formation Tracersmentioning
confidence: 98%
“…Maser science at Tidbinbilla 69 Valdettaro et al (2007) performed a high sensitivity survey of water masers in bright rimmed clouds compressed by ionization fronts from nearly massive stars. They found masers from seven bright rimmed interstellar clouds out of 44 such regions.…”
Section: Galactic Masersmentioning
confidence: 99%